Mobile tool to develop skills of communication in children with autism spectrum disorder - Guzman Condor, Raul J. (2022)
Infants with Autism Spectrum Disorder (ASD) need special therapies and tools to develop their skills. In many cases, these are not available due to socioeconomic factors, Picture Ex-change Communication System (PECS) is one of the most used tools due to its ease of use and good results. In this study we propose a methodology for developing a mobile application for interaction of infants with ASD with six phases, simultaneously we have created a technological tool called CMI, a mobile application for interaction of infants with ASD that adopts all the features of the traditional PECS and adding new functionalities. Twenty-five infants of varying severity participated in its implementation and received family support for more than a month. The results showed that there was an improvement of more than 15% in the preparation of materials, a reduction in the complexity of use and an increase in the quality of this tool compared to others. Likewise, there was a 10% increase in the development of social and communication skills, as well as a decrease in economic costs of more than 28% due to the fact that the tool is free and available to families.